KONSEP KEBAHAGIAAN PERSPEKTIF PSIKOLOGI DAN AL-QUR’AN - Anisatul Fikriyah Aprilianti, Anisatul Fikriyah Aprilianti (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2020)
The concept of happiness described in this paper is based on two perspectives, namely psychology and the al-Qur'an, then a correlation between the two results in a comprehensive understanding which is continuous. So that the concept of happiness in the Koran does not contradict, it even becomes the basis for the development of the concept of happiness in sustainable psychological theories. So that the concept of happiness in the Koran is not contradictory and even becomes the basis for the development of the concept of happiness in psychological theories. This is in line with the character so that people can achieve al-fala>h} (happiness) according to the Koran, including people who amar ma'ruf nahi munkar, do good to fellow humans and are generous to anyone who need. So that in the al-Qur'an it is explained that one of the characters so that people can achieve al-fala>h} is people who jihad (mean it) and work hard as an effort to achieve that happiness.